Identification of rRNA processing gene homologs of yeast in Neurospora crassa - S. K. Dutta; Madhu Verma; Mukesh Verma (Fungal Genetics Reports, 1987)
Identification of rRNA processing gene homologs of yeast in Neurospora crassa